A review of advanced hydrogels for cartilage tissue engineering - Ansari, Mojtaba; Darvishi, Ahmad; Sabzevari, Alireza (Frontiers in Bioengineering and Biotechnology, 2024)
With the increase in weight and age of the population, the consumption of tobacco, inappropriate foods, and the reduction of sports activities in recent years, bone and joint diseases such as osteoarthritis (OA) have become more common in the world. From the past until now, various treatment strategies (e.g., microfracture treatment, Autologous Chondrocyte Implantation (ACI), and Mosaicplasty) have been investigated and studied for the prevention and treatment of this disease. However, these methods face problems such as being invasive, not fully repairing the tissue, and damaging the surrounding tissues. Tissue engineering, including cartilage tissue engineering, is one of the minimally invasive, innovative, and effective methods for the treatment and regeneration of damaged cartilage, which has attracted the attention of scientists in the fields of medicine and biomaterials engineering in the past several years. Hydrogels of different types with diverse properties have become desirable candidates for engineering and treating cartilage tissue. They can cover most of the shortcomings of other treatment methods and cause the least secondary damage to the patient. Besides using hydrogels as an ideal strategy, new drug delivery and treatment methods, such as targeted drug delivery and treatment through mechanical signaling, have been studied as interesting strategies. In this study, we review and discuss various types of hydrogels, biomaterials used for hydrogel manufacturing, cartilage-targeting drug delivery, and mechanosignaling as modern strategies for cartilage treatment.